Design and analysis of spiral plating solution flow and rotating magnetic field device for electroplated diamond wire saw - Wei HUANG; Yanming HE; Jinbao XU; Zhenya SONG; Xiang HUANG; Yumeng SUN; Ximeng YU (Jin'gangshi yu moliao moju gongcheng)
ObjectivesIn response to the defects of diamond abrasive particle aggregation and large density fluctuations on the surface of traditional electroplated diamond wire saws, an innovative design of a combination device of spiral bath flow and rotating magnetic field is proposed to break through the technical bottlenecks of existing electroplating processes in terms of coating uniformity, orderly arrangement of diamonds and tool life. The research focuses on solving three core problems: (1) the structural design of the spiral bath flow electroplating device and the optimization of flow rate and spiral speed of the spiral bath flow; (2) the structural design of the rotating magnetic field device and the optimization of rotation speed and magnetic field strength; (3) the optimal process parameters for electroplating diamond wire saws in the new composite field electroplating device, and the production of wire saws for silicon wafer cutting experiments.MethodsThe electroplating mixture spirals in the same direction around the baseline, which can improve the consistency of diamond particle concentration around the baseline circumference and enhance the uniformity of the mixed solution stirring. Based on this, the spiral bath flow electroplating device is designed. Then the rotating magnetic field device is designed by experiment, and a suitable alternating magnetic field is applied to the plating solution, which is beneficial to improve the deposition rate and the consolidation strength of the diamond particles with the baseline. The spiral bath flow electroplating device and the rotating magnetic field device together form the electroplating combination device. Through the data accumulation of continuous experiments and production practice, the basic parameters such as permanent magnet material, magnet size, inner wall size of the glass tube, baseline travel speed, and bottom diameter of the spiral blade in the combined device are determined. The optimal technological parameters of the electroplated diamond wire saw for the combined device are obtained by the single-factor experiment method, and the wire saw is made. The surface morphologies of electroplated diamond wire saws prepared under different processes are observed by scanning electron microscope, and the monocrystalline silicon is sliced by an ultra-high speed multi-wire cutting machine. The surface roughness of the silicon wafer in the feed direction is measured by a surface roughness tester.ResultsThe mixed liquid of the spiral bath flow electroplating device enters the glass tube from the spiral blades of the spiral guide inner core, rotates spirally upward around the baseline in the glass tube under the action of the spiral blades, and flows out from the outlet of the mixed solution in the glass tube. Four symmetrical grooves are set on the inner wall of the glass tube for placing nickel anodes to avoid hindering the flow of the spiral liquid. The baseline enters from the hollow center of the spiral guide core and passes upward through the electroplating device, and the baseline is not in direct contact with the spiral guide inner core. According to the inner diameter value of the glass tube d = 56 mm, the minimum flow rate of the mixed liquid calculated is Q = 4.43 L/min. The inner core material of the spiral guide is TA2 titanium alloy, the bottom diameter of the spiral blade is 12 mm, the helix angle is 60°, the thickness is 2 mm, and the outer diameter and the height are consistent with d. The rotating magnetic field device is composed of NdFeB alloy cylinders and a fixed holder, etc., which rotates precisely around the center line of the spiral bath flow electroplating device at the appropriate rotation speed. The basic parameters of the combined device are: the magnet size is φ20 mm × 30 mm, the inner wall diameter × length of the glass tube is φ56 mm × 850 mm, the baseline travel speed is less than or equal to 20 m/min, the bottom diameter of the spiral blade is 5 mm, the blade thickness is 2 mm, and the concentration of diamond abrasive is 1.55 g/L. The optimal process parameters for electroplating diamond wire saws in the combination device, determined by single-factor experiment are: the spiral blade number is 5, the spiral angle is 60°, the mixed liquid flow rate is 4.80 L/min, the fixed holder number is 12, the staggered arrangement angle of the permanent magnets is 60°, the magnetic field rotation speed is 60 r/min, and the magnetic field strength of the N38M permanent magnet is 0.549 T. The electroplating line produced under the optimal process parameters shows that the diamond particles are evenly distributed on the baseline surface without any stacking or agglomeration phenomenon, and the particle distribution density is basically uniform. The number of diamond particles is 15 to 25 particles/mm, and the fluctuation range of diamond particle numbers is controlled within 11 particles/mm. Using this wire saw to slice a single crystal silicon rod with φ50.6 mm, the surface roughness Ra value of the silicon wafer in the feed direction is 0.583 μm, which is 35.9% and 28.2% lower than the literature values, respectively.ConclusionsThe combined device of spiral bath flow and rotating magnetic field is designed to make the diamond abrasive particles in the mixed liquid evenly distributed in the bath flow mode, and orderly arranged according to the magnetic field line and rotated around the baseline. This can basically eliminate the diamond agglomeration defect on the surface of the wire saw and improve the uniformity of the distribution density of diamond particles. The average surface roughness of the silicon wafer in the feed direction is lower, so the workload of the subsequent grinding process can be reduced.